Supplier empowerment: Mediating situational factors and perceived performance. Issue 3 (June 2020) - Liao, Kun; Deng, Xiaodong; Liao, Ying; Zhang, Qingyu
Abstract: The understanding of the behavioral and cognitive factors that affect organizations' performance has attracted increasing attention of scholars and practitioners. Based on the literature of psychological empowerment at the individual and the team levels, this study develops the concept of supplier empowerment in the context of purchasing and supply management. Further, this study proposes a research model that explores the role of supplier empowerment as a cognitive concept in mediating the relationship between situational factors (a supplier's process modularity and the mutual trust with its customers/buyers) and the supplier's perceived performance in its operations and customer service. This model is tested with 208 responses from automotive industry suppliers. The findings highlight the importance of empowered suppliers in decreasing inventory levels and increasing order fulfillment performance. Highlights: An empirical study based upon empowerment theory at both the individual and the team levels and extends the empowerment concept to the purchasing and supply management context. From supplier's perspective, the research model investigates the role of supplier empowerment as a cognitive concept in mediating the relationship between situational factors (a supplier's process modularity and the mutual trust with its customers/buyers) and the supplier's perceived performance. The findings highlight the importance of empowered suppliers in decreasing perceived inventory levels and increasing perceived order fulfillment performance.